2015
DOI: 10.1186/s13104-015-1189-6
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of a geriatric nurse practitioner in a multidisciplinary diagnostic service for people with cognitive disorders

Abstract: BackgroundThe aim of the study was to evaluate whether adding a geriatric nurse practitioner (GNP) to an outpatient diagnostic multidisciplinary facility for patients with cognitive disorders (Diagnostic Observation Center for PsychoGeriatry, DOC-PG) could improve quality of care. DOC-PG combines hospital diagnostics and care assessment from a community mental health team and provides the general practitioner (GP) with advice for treatment and management. In a previous study, we found that 28.7% of the advice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Thus, we suggest that there is an important role for co-ordinated care by a trained dementia practitioner, 346 as there appears to be a skill gap related to the management of dementia and CB in the current workforce. Given our observations on the differing contextual resources required for delivery within care homes and family care settings, a priority for service improvements for effective management of dementia and CB is the development of separate service models for care home and family care settings within which specialist dementia practitioners may be trained and resourced to have clarity of purpose in their goals for patient care and related contextual outcomes.…”
Section: Overview Of Key Findings From Challenge Demcarementioning
confidence: 93%
“…Thus, we suggest that there is an important role for co-ordinated care by a trained dementia practitioner, 346 as there appears to be a skill gap related to the management of dementia and CB in the current workforce. Given our observations on the differing contextual resources required for delivery within care homes and family care settings, a priority for service improvements for effective management of dementia and CB is the development of separate service models for care home and family care settings within which specialist dementia practitioners may be trained and resourced to have clarity of purpose in their goals for patient care and related contextual outcomes.…”
Section: Overview Of Key Findings From Challenge Demcarementioning
confidence: 93%
“…Seven publications were randomized controlled trials (Amjad et al, 2018;Donath et al, 2010;Lawton et al, 1989;McCallion et al, 2004;Newcomer et al, 1999;Vickrey et al, 2006;Weinberger et al, 1993). Three were non-randomized controlled trials (Ament et al, 2015;Bass et al, 2013;Romero et al, 2007). Six publications were one-group pretestposttest trials (Aranda et al, 2003;Emme von der Ahe et al, 2011;Emme von der Ahe et al, 2010;Lathren et al, 2013;Lee et al, 2014;Tompkins & Bell, 2009).…”
Section: Study Setting and Designmentioning
confidence: 99%
“…Two of the studies had no effect on relevant outcomes; one was a referral-focused intervention (Ament et al, 2015), the other used monetary support in combination with case management (Lawton et al, 1989) (table 1).…”
Section: Effects Of the Various Interventionsmentioning
confidence: 99%
“…For example, individuals with diabetes generally experienced reduced HbA1cs (Chang, Davis et al 2007, Stone, MacPherson et al 2010, Choi and Rush 2012, Jessee and Rutledge 2012 while other individuals reported an improvement in symptoms specific to their disease process (Philp, Lucock et al 2006, Wright, Purdy et al 2007, Owens, Eby et al 2012, Sawatzky, Christie et al 2013, Voorn, Vermeulen et al 2013, Housholder-Hughes, Ranella et al 2015, Kozlowski, Lusk et al 2015, Teunissen, Stegeman et al 2015. In some studies caregivers also benefitted from the nurse practitioner intervention, such as caregivers of patients with dementia who reported a reduced caregiver burden (Ament, Wolfs et al 2015).…”
Section: Individual Benefitsmentioning
confidence: 99%